Gas Discharge Plasmas and Their Applications (GDP 2015) 12th International Conference, September 6-11, 2015, Tomsk, Russia abstracts - Korolev electrophysicist Professor of Tomsk Polytechnic University, Doctor of physical and mathematical sciences; Koval specialist in the field of electronics Professor of Tomsk Polytechnic University, Doctor of technical sciences (Publishing House of IAO SB RAS, 2015)
This book contains abstracts of oral and poster reports presented at the International conference GasDischarge Plasmas and Their Applications (GDP 2015). This conference is a continuation of a series ofconferences held in Russia since 1984, as well as seminars and conferences on the technological applicationsof low-temperature plasma traditionally held in Tomsk. The conference program covers a wide range oftechnical areas and modern aspects of the physical processes in the generators of low-temperature plasma,low-pressure and high-pressure discharges, pulsed plasma sources, surface modification, and other gasdischarge technologies.